2021
DOI: 10.1021/acs.orglett.1c00751
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Thiazole-2-thiones through TBPB-Promoted Oxidative Cascade Cyclization of Enaminones with Elemental Sulfur

Abstract: An unprecedented method for the construction of thiazole-2-thiones via an oxidative cascade cyclization strategy is described. The novel protocol involves the simultaneous formation of two CS bonds and a CS bond on the structure of enaminones in a single operation through a cascade of C­(sp2)H/C­(sp3)H bond sulfurations and C­(sp3)–H bond thiocarbonylation. This transformation allows for the efficient synthesis of thiazole-2-thiones with broad tolerance in moderate to excellent yields from simple enaminone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…CvN double bonds, 39,40 isocyanides, 29,37,[41][42][43] isothiocyanates 44 and iodonium salts. 45 Recently, a handful of new methods exploited the divergent reactivity of chalcones 36,[46][47][48][49] and β-oxo-enamines 35,[50][51][52][53][54] towards sulfur giving access to the selective formation of sulfur containing heterocycles and other structures (Scheme 2). In fact, Retailleau and Nguyen demonstrated that starting from chalcones, the careful selection of the base may enable the selective formation of either sultams or benzothiophenes.…”
Section: Papermentioning
confidence: 99%
“…CvN double bonds, 39,40 isocyanides, 29,37,[41][42][43] isothiocyanates 44 and iodonium salts. 45 Recently, a handful of new methods exploited the divergent reactivity of chalcones 36,[46][47][48][49] and β-oxo-enamines 35,[50][51][52][53][54] towards sulfur giving access to the selective formation of sulfur containing heterocycles and other structures (Scheme 2). In fact, Retailleau and Nguyen demonstrated that starting from chalcones, the careful selection of the base may enable the selective formation of either sultams or benzothiophenes.…”
Section: Papermentioning
confidence: 99%
“…Actually, both transformation modes have found broad and significant application in devising highly enriched synthetic methods. The reactions employing enaminones as CC–N building blocks without cleaving the C–N bond have been successfully utilized for the synthesis of diverse organic compounds such as pyrroles and derivatives, 2 oxazoles, 3 imidazoles, 4 thiazoles, 5 triazoles, 6 indoles, 3 d ,7 pyridinones, 8 quinolones, 8 b pyrimidines, 9 triazines 10 and other nitrogen-containing compounds. 11 Research advances on such reactions of enaminones have just been reviewed by Xia and Niu.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur-containing heterocycles as an important class of compounds show significant potential for their multiple functions, especially exhibit attractive biological and pharmacological properties, such as anti-inflammatory, antimicrobial, anti-tuberculosis, and anti-HIV activity, etc. [1][2][3] Therefore, the synthesis of sulfur-containing heterocyclic compounds has attracted great attention in modern organic chemistry. [4][5][6][7] Different sulfur sources, [8] e. g., potassium sulfide, [9] thiocyanate, [10] thiourea, [11] isothiocyanate, [12] thioamide, [13] thiophenol, [14] and elemental sulfur (S 8 ), [15] can be used to construct sulfur-containing heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur‐containing heterocycles as an important class of compounds show significant potential for their multiple functions, especially exhibit attractive biological and pharmacological properties, such as anti‐inflammatory, antimicrobial, anti‐tuberculosis, and anti‐HIV activity, etc [1–3] . Therefore, the synthesis of sulfur‐containing heterocyclic compounds has attracted great attention in modern organic chemistry [4–7] .…”
Section: Introductionmentioning
confidence: 99%